Permisive Parenting and Extrovert Personality With Consumtive Behavior in Indonesian Workers (TKI / TKW) Children in Bandung Tulungagung District - Malik Maya Faisati; IGAA. Noviekayati; Amanda Pasca Rini (PSIKODIMENSIA, 2018)
The purpose of this study was to examine the relationship between permissive parenting and extroverted personality with consumptive behavior in TKI / TKW children in Bandung Tulungagung District. The research subjects were 70 students of class X and XI of SMK Negeri 1 Bandung Tulungagung. The research method uses Quantitative by using Non-Parametric Kendall analysis. Based on the analysis, it was obtained results that permissive parenting and extroverted personality with consumptive behavior had a significant correlation. Extroverted personality with consumptive behavior has a significant relationship, but permissive parenting with consumptive behavior is not significantly associated